Childhood adversities are associated with shorter leukocyte telomere length at adult age in a population-based study. (August 2021) - Ämmälä, Antti-Jussi; Suvisaari, Jaana; Kananen, Laura; Lönnqvist, Jouko; Ripatti, Samuli; Pirkola, Sami; Paunio, Tiina; Hovatta, Iiris
Abstract: Telomeres are repeat sequences and an associated protein complex located at the end of the chromosomes. They shorten with every cell division and are regarded markers for cellular aging. Shorter leukocyte telomere length (LTL) has been observed in many complex diseases, including psychiatric disorders. However, analyses focusing on psychiatric disorders are mainly based on clinical samples and the significance of shorter LTL on the population level remains uncertain. We addressed this question in a population-based sample from Finland (N = 7142). The survey was performed and the blood samples were collected in 2000–2001 to assess major public health problems and their determinants. DSM-IV diagnoses of major psychiatric illnesses were obtained by interview using the Composite International Diagnostic Interview. Information regarding their risk factors, including the number of self-reported childhood adversities, recent psychological distress, and sleep difficulties was collected by questionnaires. LTL was measured by qPCR. None of the studied psychiatric illnesses, sleep difficulties, or recent psychological distress associated with LTL. However, individuals with three or more childhood adversities had shorter LTL at adult age (β = −0.006, P = 0.005). Also, current occupational status was associated with LTL (β = −0.03, P = 0.04). These effects remained significant after adjusting for known LTL-associated lifestyle or sociodemographic factors. In conclusion, relatively common childhood adversities were associated with shorter LTL at adult age in a nationally representative population-based cohort, implying that childhood adversities may cause accelerated telomere shortening. Our finding has potentially important implications as it supports the view that childhood adversities have an impact on psychological and somatic well-being later in life. Highlights: Current psychiatric illnesses or sleep did not associate with LTL in a large nationally representative population cohort. Childhood adversive experiences associated with LTL in adulthood independently from lifestyle or socioeconomical factors. Also occupational status in adulthood associated with LTL independently.